The Effect of Fermentation Time on Antioxidant Activity of Vanilla (Vanilla planifolia) Leaf Kombucha Tea - Agustina, Eva; Purnamasari, Risa; Kusumawati, Estri; Nafisah, Raihana Frika; Shofiyya, Ainina Neihayatus; Tyastirin, Esti (International Conference on Sustainable Health Promotion, 2023)
Free radicals can come from exposure to pollution such as motor vehicle fumes, industrial fumes, heavy metal contamination and consumption of unhealthy food and drinks. One of the innovations in beverage products that are rich in antioxidants and popular with the public is kombucha tea. Plant leaves that have the potential to be used as basic ingredients for making kombucha tea are vanilla leaves (Vanilla planifolia). The purpose of this study was to determine the effect of the length of fermentation time on the manufacture of vanilla leaf kombucha tea on antioxidant activity. The research method used was experimental research by the titrated total acid content test, pH test and levels of antioxidants of kombucha tea vanilla leaves test with variations of 0, 4, 8, and 12 days. The results of this study obtained IC50 value was 18% on day 0.